Doherty amplifier and antenna combiner - Pereira, Joana Lopes Silva (2019)
The conventional Doherty architecture is commonly used in wireless transmitters for its ability to boost the average efficiency of a traditional single-ended class B amplifier. It consists of two parallel single-ended amplifying branches (named carrier and peaking amplifiers) which are linked, at the output, through a /4 combiner. This output combiner commonly has a significant impact on the overall bandwidth, as it is usually built from a transmission line structure with tuned dimensions. Other non-conventional combining structures could be designed, targeting a wider bandwidth, contributing to an overall increase of the Doherty amplifier’s bandwidth. Being this an high relevance research topic for the development of high efficient and broadband amplifiers, it is highly desirable to have a laboratory setup that implements a Doherty power amplifier to which distinct output combiner structures can be connected and tested. In that sense, the design of two single-ended amplifiers (the carrier and the peaking) was performed in a circuit simulator (ADS, from Keysight) together with the input power divider that compose the Doherty architecture. The Doherty amplifier main board was designed to incorporate the carrier and peaking amplifiers, and also the power splitter at the input, and it was prepared so that it could be connected to any desired combiner to be tested. A traditional Doherty power combiner was designed and both boards (Doherty amplifier and the combiner) were produced, connected and tested in the RF laboratory. The measured amplifier presented the typical caractheristics of a Doherty amplifier with nearly 75% of drain efficiency at full-power, and nearly 50% at the output back-off level. In addition, a second combiner unit was designed with two purposes. The first was to demonstrate the operation of the designed Doherty amplifier with a distinct output combiner, showing that, as intended in this work, it is suited to test multiple combiner structures. The second objective was to serve as preliminary test to evaluate the possibility of merging the output combiner with the antenna element. Taking advantage of the electromagnetic coupling between antennas, this second combiner structure uses two antenna elements that were tuned to simultaneously behave as output combiner of the Doherty amplifier and a radiating element.